2013
DOI: 10.1021/jf402591f
|View full text |Cite
|
Sign up to set email alerts
|

Bovine Milk Fat Globule Membrane Proteins Are Affected By Centrifugal Washing Processes

Abstract: The impact of washing on the release of proteins from the milk fat globule membrane (MFGM) was examined by applying washing procedures with different degrees of stringency to milk fat globule (MFG) surfaces in simulated milk ultrafiltrate buffer solution. Three washing methods, M1 (3000g, 5 min, three washes), M2 (3750g, 15 min, one wash), and M3 (15000g, 20 min, three washes) were chosen. MFG ζ-potential increased after M3 washing (P < 0.05), suggesting surface damage. For M1, in which the native MFG surface … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 48 publications
4
27
0
1
Order By: Relevance
“…This was explained by the possibility of membrane component reorganisation after the drastic processing impact of homogenisation. Zheng, Jim enez-Flores, and Everett (2013) showed using CLSM that structural changes to the MFGM took place after washing of cream (see Fig. 6).…”
Section: Structural Arrangement Of Mfgm Proteinsmentioning
confidence: 98%
See 3 more Smart Citations
“…This was explained by the possibility of membrane component reorganisation after the drastic processing impact of homogenisation. Zheng, Jim enez-Flores, and Everett (2013) showed using CLSM that structural changes to the MFGM took place after washing of cream (see Fig. 6).…”
Section: Structural Arrangement Of Mfgm Proteinsmentioning
confidence: 98%
“…Britten et al (2008) showed that the total protein content of buttermilk (including caseins, whey proteins, and MFGM proteins) was reduced from 24.5 g L À1 to 5.2 g L À1 after one washing step with 10 times the starting volume of UF Saline solution (0.9% NaCl) Cavaletto et al, 1999;Cebo et al, 2010;Fortunato et al, 2003;Keenan et al, 1971;Patton, 1982 Phosphate Cavaletto et al, 1999;Cebo et al, 2010;Dickow et al, 2011;Horisberger et al, 1977;Kathriarachchi et al, 2014;Liao et al, 2011;Mather & Keenan, 1975;Nejjar et al, 1986;Ong et al, 2010;Patton, 1982;Patton & Huston, 1986;Sharma et al, 1996;Ye et al, 2002;Zamora et al, 2012;Zheng et al, 201330e45 C Jenness & Palmer, 1945Montagne et al, 1999;Oehlmann et al, 1994;Shimizu & Yamauchi, 1982;Wiese & Palmer, 1932 1000e3000 (low) Cavaletto et al, 1999;Cebo, Caillat, Bouvier, & Martin, 2010;Chien & Richardson, 1967;Dalgleish & Banks, 1991;Dickow, Larsen, Hammershøj, & Wiking, 2011;Fortunato et al, 2003;Horisberger et al, 1977;Iametti et al, 1997;Kathriarachchi et al, 2014;…”
Section: The Impact Of Washing On Fat Globules and The Mfgmmentioning
confidence: 99%
See 2 more Smart Citations
“…Experimental setup of cream washing using a pilot scale cream separator.Measurements of MFGM proteins with SDS-PAGE and LC-MS/MS have shown that even integral MFGM proteins were depleted by washing procedures(Le et al, 2013;Zheng, Jim enez-Flores, & Everett, 2013).…”
mentioning
confidence: 99%